Kitchen science experiments : how does your mold garden grow? - Bardhan-Quallen, Sudipta (Mad science (Sterling Publishing Company), 2010)
Introduces basic chemistry concepts that can be learned in everyday kitchens, with easy-to-follow instructions and scientific explanations for each experiment.